TRANSLATION EQUIVALENCE AND TRANSLATABILITY: A THEORETICAL REASSESSMENT - Oybekova Gulnoza Oybek qizi (Research Focus International Scientific Journal, 2026)
This article provides a theoretical reassessment of translation equivalence and translatability, which are central concepts in translation studies. It critically examines classical and contemporary views on equivalence, untranslatability, and the limits of transferring meaning between source and target texts. Translation is seen as a dynamic interpretative process instead of a fixed match between language units. Through qualitative theoretical analysis, the article combines linguistic, functional, and cultural approaches to translation. The analysis shows that equivalence should not mean exact sameness; it is a relative and context-dependent relationship influenced by textual function, audience expectations, and cultural norms. The findings suggest that claims of absolute untranslatability are mostly theoretical, as translators use various strategies to bridge linguistic and cultural gaps. This article argues that translation adequacy relies on functional and pragmatic alignment, rather than strict formal replication, leading to a more flexible understanding of translation across different fields.